Where SLA and Language Education Meet: The Transfer from Task-Based Needs Analysis to Task Design - Roger Gilabert (MDPI AG, 2023)
This theoretical article sets a goal to investigate how task-based needs analysis (TBNA) as part of instructed second language acquisition (ISLA) may mediate between constructs and concepts in second language acquisition (SLA) and task-based design. It is claimed that as an instantiation of instructed second language acquisition (ISLA), TBNA in task-based language teaching (TBLT) may bring together decision-making during task design and what is known about SLA products and processes. The article then explores some of the key SLA concepts in ISLA around the constructs of input, intake, knowledge, and output and relates them to task-based research. Thirdly, TBNA is defined and analyzed in terms of how it may inform task and syllabus design. Finally, SLA constructs are directly associated with pedagogic task design that springs from TBNA. After a close inspection of all dimensions of TBNA, the article concludes that task design based on detailed TBNA has indeed the potential to bring reality into instruction through thorough task descriptions and methods, as well as to trigger well-known and specific processes that bring SLA and language education closer.